2000
DOI: 10.1097/00000433-200003000-00004
|View full text |Cite
|
Sign up to set email alerts
|

Advances in the Diagnosis of Wound Vitality

Abstract: The diagnosis of the vital origin of wounds in many cases remains an unsolved problem for the forensic pathologist. Practical experience enables the expert to diagnose the vital or postmortem origin of wounds on the basis of macroscopic examination. In some cases, optic microscopy is used to confirm the diagnosis. In many other cases, additional more sensitive and specific markers of vitality are required. In the past 50 years, comprehensive research on this topic has resulted in a better understanding of the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
23
0
2

Year Published

2003
2003
2017
2017

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(26 citation statements)
references
References 54 publications
1
23
0
2
Order By: Relevance
“…As skin covers the outer surface of the body, it is the most vulnerable part, and dermal wound age is a critical issue in routine forensic autopsies. Inflammatory cell dynamics [1] and enzyme activities, such as ATPase, acid phosphatase, and alkaline phosphatase [10] are still applied to wound age estimation. Analyses of cytokine expressions in murine skin and immunohistochemical detection in human skin have also been reported, and their usefulness for dermal wound age estimation has been suggested [9,16,22,31,32].…”
Section: Introductionmentioning
confidence: 99%
“…As skin covers the outer surface of the body, it is the most vulnerable part, and dermal wound age is a critical issue in routine forensic autopsies. Inflammatory cell dynamics [1] and enzyme activities, such as ATPase, acid phosphatase, and alkaline phosphatase [10] are still applied to wound age estimation. Analyses of cytokine expressions in murine skin and immunohistochemical detection in human skin have also been reported, and their usefulness for dermal wound age estimation has been suggested [9,16,22,31,32].…”
Section: Introductionmentioning
confidence: 99%
“…The evolution of human skin lesions with time, and therefore, the relationships between the aspect of lesions and the time from trauma to death, is a major problem in forensic medicine, which is addressed on the basis of the normal wound healing process [1,2]. Histamine levels in skin vary appreciably early after wounding [3,4]; in particular, they increase significantly between 5 min and 3 h after trauma and decrease afterwards until 24 h [5].…”
Section: Introductionmentioning
confidence: 99%
“…For the discrimination of antemortem and postmortem wounds, various methods have been reported (Bonelli et al 2003, Ortiz-Rey et al 2003, Baroldi et al 2001, Hernandez-Cueto et al 2000, Ortmann et al 2000. Bonelli et al showed that the detection of mast cells with immunohistochemical techniques can lead to a high level of discrimination between antemortem and postmortem lesions, and Ortiz-Rey et al analyzed the expression of fibronectin and tenascin in wounds.…”
Section: Introductionmentioning
confidence: 99%